Analisis dinamico de los sistemas integrales de produccion en pequeñas fincas, del recinto Tierra Colorada del canton Mocache, provincia de Los Rios, 2015-2016 - Quinteros Laborde, Lastenia Johanna (2016)
The research was carried out on site Tierra Colorada, located in the canton Mocache Los Rios Province, it has a tropical climate that varies between 23 and 33 ° C. The variables evaluated were: Determine the costs and revenues generated by integrated systems of production; Identify agricultural production systems; Diagnose the socioeconomic situation in which farmers live enclosure. Production records and income of the agricultural and livestock components were reviewed. With information from 20 surveys where it was determined: The income of farmers mainly depend on the cultivation of cocoa, which generates higher profits on average is $ 4530 in the year with a cost benefit ratio of 3.8; `means that for every dollar they invest earn $ 2.8. Instead corn production profits will average $ 1380 a year with a cost benefit ratio of 1.3. Moreover the production of poultry and other animal species have only for their own consumption although often sell to cover any need, although there are two families raising pigs and chickens shed for sale. 30% of farmers develop other activity outside the farm. Applying the financial index: Benefit / Cost (B / C). Small farms generate income sustainably exploiting natural resources. For this it is important to have knowledge about architecture in crops (association and crop rotation); as crop associations are effective low-cost alternatives to increase productivity planting; It is then, a practice where two or more species in the same field in order to sow mutual benefit. The advantage integral farm small areas by using efficient technology, integrating different areas systematically and combining agricultural crops with livestock that benefit the soil and at the same time allow good weed management.